Evaluating the Effectiveness of Social Forestry: A Meta-Analysis of Policy Documents and Implementation - Ardyanto, Niko; Wulandari, Christine; Bakri, Samsul; Febryano, Indra Gumay (Jurnal Pemerintahan dan Kebijakan (JPK), 2026)
This study evaluates the effectiveness of Indonesia’s Social Forestry (SF) policy implementation from 2016 to 2024 through a document-based meta-analysis and systematic literature review. The policy, initiated under Ministerial Regulation No. P.83/2016, aims to address forest tenure inequality and improve community welfare through legal access to forest management. A total of 23 documents, including official government reports, NGO evaluations, and peer-reviewed publications, were analyzed using descriptive quantitative and thematic qualitative methods. The findings reveal that Social Forestry has significantly expanded legal access to forest areas, reaching over 8 million hectares through approximately 11,000 decrees, and has generated positive economic, social, and environmental outcomes. The program enhanced household income, strengthened institutional participation, and promoted conservation practices such as agroforestry and forest zoning. However, implementation effectiveness remains constrained by weak institutional capacity, limited financing, inconsistent data integration, and inadequate cross-sectoral coordination. Strengthening local institutions, establishing interoperable reporting systems, and developing community enterprises through digital and market-based incentives are essential for long-term sustainability. The study concludes that the success of Social Forestry depends on collaborative governance and adaptive policies that balance administrative expansion with substantive socio-ecological outcomes.